2019
DOI: 10.1016/j.chom.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Factors Required for Transmission of Streptococcus pneumoniae in Mammalian Hosts

Abstract: The capacity of Streptococcus pneumoniae to successfully transmit and colonize new human hosts is a critical aspect of pneumococcal population biology and a prerequisite for invasive disease. However, the bacterial mechanisms underlying this process remain largely unknown. To identify bacterial factors required for transmission, we conducted a high-throughput genetic screen with a transposon sequencing (Tn-seq) library of a pneumococcal strain in a ferret transmission model. Key players in both metabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 39 publications
1
46
0
Order By: Relevance
“…1A ). The desiccation resistance conferred by the IAV-bacterium complex was independent of bacterial viability, as ethanol-killed pneumococci, or a Δ spxB mutant, which maintains higher desiccation viability than wild-type pneumococcus ( 41 ), promoted influenza viability to a degree equivalent to that seen with live wild-type S. pneumoniae ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1A ). The desiccation resistance conferred by the IAV-bacterium complex was independent of bacterial viability, as ethanol-killed pneumococci, or a Δ spxB mutant, which maintains higher desiccation viability than wild-type pneumococcus ( 41 ), promoted influenza viability to a degree equivalent to that seen with live wild-type S. pneumoniae ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 97%
“…It should also be noted that we utilized relatively young ferrets aged 9 weeks, while many other investigations querying influenza transmission routinely utilized ferrets of 4 to 12 months of age ( 24 26 ). The utilization of younger ferrets was primarily due to previous work demonstrating that ferrets in this age group rapidly transmit S. pneumoniae by both contact and aerosol routes ( 4 , 41 ). Whether our findings would extend to older ferrets that likely have distinct microbial community composition remains an unresolved but intriguing issue.…”
Section: Discussionmentioning
confidence: 99%
“…Countless global datasets are available for diverse bacterial organisms including Gram-positive species. For example, high-resolution transcriptomics, transposon mutagenesis, and Grad-seq data exist for Streptococcus pneumoniae (Aprianto et al, 2016(Aprianto et al, , 2018Hor et al, 2020;Rowe et al, 2019;van Opijnen and Camilli, 2012;Warrier et al, 2018). More generally, various transposonsequencing approaches have been applied to bacterial pathogens under virulence conditions (Karlinsey et al, 2019;Rendón et al, 2020;Warr et al, 2019), and dual RNAseq has become the gold-standard to chart the transcriptional landscape of pathogens during infection (Montoya et al, 2019;Pisu et al, 2020;Ritchie and Evans, 2019;Westermann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mitsi et al further demonstrated that the agglutinating activity of antibodies generated by vaccination with capsule were critical to protection against acquisition of carriage in a human challenge model [6]. An interesting twist to this emerging story is the recent demonstration that the influenza virus can hitchhike on aggregated pneumococci, and thus strongly enhance transmission of both pathogens [7]. It stands to reason that agglutinating activity could be a major predictor of the ability of antibodies to protect from spreading disease, and that distinguishing antibodies that protect in sepsis vs. colonization/transmission may require very different assays.…”
Section: Multi-modal Protection: Anti-capsular Antibodies Are Not Jusmentioning
confidence: 99%
“…Many proteins and signaling molecules, such as PsrP, GlpO, BriC, CbpD, LytC, and CbpF, can be targeted to interrupt the participation of these processes in biofilms and colonization. Others approaches involve distinguishing the features of bacteria shed from biofilms that then move on to produce disease in other organs or enhance transmission [7,37].…”
Section: Multi-modal Protection: Protein Functions Enter the Vaccine mentioning
confidence: 99%